2021
DOI: 10.1039/d1na00285f
|View full text |Cite
|
Sign up to set email alerts
|

NIR luminescence lifetime nanothermometry based on phonon assisted Yb3+–Nd3+energy transfer

Abstract: Luminescence thermometry in biomedical sciences is highly desirable, but also highly challenging and demanding technology. Numerous artifacts have been found during steady-state spectroscopy temperature quantification, such as ratiometric spectroscopy. Oppositely,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…252 The phonon-assisted energy transfer in Yb/Nd couples is also capable of enabling NIR lifetime nanothermometry. 253 Recent work suggests that the decay time of the 3 H 4 state of Tm 3+ can improve the nanothermometry in the first biological window. 254 These optical parameters have been well utilized for temperature sensing, however, it should be noted that further improving thermal sensitivity is still a challenge.…”
Section: Integrated Optical Imaging Toolboxesmentioning
confidence: 99%
“…252 The phonon-assisted energy transfer in Yb/Nd couples is also capable of enabling NIR lifetime nanothermometry. 253 Recent work suggests that the decay time of the 3 H 4 state of Tm 3+ can improve the nanothermometry in the first biological window. 254 These optical parameters have been well utilized for temperature sensing, however, it should be noted that further improving thermal sensitivity is still a challenge.…”
Section: Integrated Optical Imaging Toolboxesmentioning
confidence: 99%
“…Thus, lifetime‐based in vivo temperature monitoring of LLNs has been gaining increasing attention in recent years due to its anti‐interference merit in complex biological environment, while the lifetime and emission intensity of LLNs can be further optimized for boosting thermometric performance through exploring fabrication strategies. On the other hand, the emission wavelength for lifetime detection currently lies in around 1000 nm with Yb 3+ /Nd 3+ pair [14g,17b,c] . For the future development of τ‐NT, more efforts are needed to exploit the emissions at longer wavelengths with less scattering (e. g. the ones at NIR‐II BW) for lifetime detection.…”
Section: Introductionmentioning
confidence: 99%
“…As our previous studies have shown, the chemical composition of the host material significantly affects the thermometric parameters in APO 4 :Nd 3+ ,Yb 3+ (A = Y, Lu, La, Gd). 25 …”
Section: Introductionmentioning
confidence: 99%
“…As our previous studies have shown, the chemical composition of the host material significantly affects the thermometric parameters in APO 4 :Nd 3+ ,Yb 3+ (A = Y, Lu, La, Gd). 25 In this work, the effect of the synthesis parameters on the morphology of YPO 4 :Nd 3+ ,Yb 3+ nanocrystals and their consequences on the thermometric parameters of the phosphor are analyzed. For this purpose, the solvothermal synthesis method in a mixture of ethanol and oleic acid was used.…”
Section: Introductionmentioning
confidence: 99%